395 Exercise Capacity is Maintained in Older Military Personnel with Moderate to Severe Obstructive Sleep Apnea. (3rd May 2021) - Arora, Subodh; Powell, Tyler; Foster, Shannon; Hansen, Shana; Morris, Michael
Abstract: Introduction: The relationship between moderate to severe OSA and exercise capacity remains unclear. Prior studies showing a reduction in VO2 max in this population have mostly involved middle-aged and overweight patients. We looked to determine if this trend in VO2 max was present in a similarly aged population of military personnel with previously undiagnosed moderate to severe OSA. Methods: We studied 170 middle-aged male military members who underwent cardiopulmonary exercise testing (CPET) and polysomnography (PSG) as a part of a comprehensive evaluation for an established military program. For analysis, patients were categorized either into an OSA group (apnea-hypopnea index (AHI) ≥ 15 events/h) or control group (AHI < 15 events/h). VO2 max was compared between groups. Results: Mean AHI was 29.0 in the OSA group (n =58) versus 7.4 in the controls (n = 112). Patients were of similar age (53.1 vs. 53.7 years) and BMI was slightly higher in the OSA group (27.5kg/m2 versus 26.3 kg/m2, P = .0077). Percent-predicted VO2 max was supernormal in both groups, though was comparatively lower in the OSA group (117% vs. 125%; P <.001). There was a trend toward a blunted heart rate response to exercise in the OSA group as represented by peak heart rate (163 vs. 178; p=0.07). Conclusion: Older military personnel with moderate to severe OSA have normal exercise capacity. This may suggest that the low-arousal OSA phenotype often noted in military personnel does not significantly influence exercise capacity or that regular exercise helps limit its impact. It remains likely that the effect of untreated OSA on exercise capacity is influenced by several variables including age, BMI, OSA phenotype, and regularity of exercise. Trends in VO2 max and peak heart rate noted in this study may suggest that untreated OSA in certain populations can negatively impact exercise capacity Support (if any): No external funding